2014
DOI: 10.1111/trf.12819
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three noninvasive methods for hemoglobin screening of blood donors

Abstract: Noninvasive Hb tests represent an attractive alternative by eliminating pain and reducing risks of blood contamination. The main problem for generating reliable results seems to be preanalytical variability in sampling. Despite the sensitivity to environmental stress, all methods are suitable for Hb measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 27 publications
(55 reference statements)
5
44
3
Order By: Relevance
“…Studies from Italy, Germany and France involved a fairly equal number of men and women reporting to blood donation centres, but anaemia prevalence is much lower in these countries compared to India. The German study reported a mean Hb value of 13.4 g/dL (SD 0.93) in women (using the gold standard, Sysmex KX-21),12 while in our study settings in rural India the mean Hb was 10.0 g/dL (using the gold standard, Sysmex XP-100). Similarly, the mean Hb in the French study was 13.2 g/dL (95% CI 11.9 to 14.3),1 and in the Italian study the boxplot indicated a mean Hb of 14.0 g/dL 15.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Studies from Italy, Germany and France involved a fairly equal number of men and women reporting to blood donation centres, but anaemia prevalence is much lower in these countries compared to India. The German study reported a mean Hb value of 13.4 g/dL (SD 0.93) in women (using the gold standard, Sysmex KX-21),12 while in our study settings in rural India the mean Hb was 10.0 g/dL (using the gold standard, Sysmex XP-100). Similarly, the mean Hb in the French study was 13.2 g/dL (95% CI 11.9 to 14.3),1 and in the Italian study the boxplot indicated a mean Hb of 14.0 g/dL 15.…”
Section: Discussioncontrasting
confidence: 56%
“…Second, our study recorded a good response rate (96.8%), with only seven eligible women declining to participate. Lastly, the non-invasive readings were obtained in accordance with the manufacturer's guidelines, and none of our subjects had thumb deformity, infection, ulcerations, oedema or skin colourants such as henna (locally known as Mehndi) 12. However, a technical failure of the non-invasive sensor occurred twice during the study, which delayed data collection, and caused the loss of two samples as mentioned before.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current investigation was integrated into a larger study pertaining to efficacy, safety, and pharmacodynamics of praziquantel in preschool-aged (2-5 years) and schoolaged (6)(7)(8)(9)(10)(11)(12)(13)(14)(15) The study staff was skilled at both Hb measuring systems. The same study staff used the Hb-measuring devices throughout the study.…”
Section: Methodsmentioning
confidence: 99%
“…Several devices are now commercially available and have been studied in a variety of settings with somewhat mixed results when compared with both invasive point-of-care devices and venous blood samples processed on a laboratory analyzer. [11][12][13][14][15] A recent meta-analysis identified 39 relevant studies and concluded that noninvasive Masimo Pronto-7 ® devices provide an unbiased, pooled estimate of laboratory Hb, yet have lower precision and wider 95% limits of agreement than invasive HemoCue devices. 16 Representative data on anemia are sparse in settings where anemia is most prevalent and particularly in settings without clinical facilities, where noninvasive methods are welcomed by both patients and medical personnel.…”
Section: Introductionmentioning
confidence: 99%